A New Approach to Obtaining N ?-t-Boc-Amino Acid Aldehydes from Asparagine and Glutamine for Reduced Amide Pseudopeptide Solid-Phase Synthesis (2011)
Reduced amide pseudopeptides have been proposed as structural probes that could be useful as potential malarial vaccine components. However, designing determined pseudopeptide sequences containing isoster peptide bonds, either on an asparagine (Asn) or on a glutamine (Gln) residues, can become difficult because these precursor amino acid aldehydes are obtained in yields lower than 0.5%. This work presents a new strategy for obtaining both Asn and Gln aldehydes based on a controlled side-chain protection approach as well as a suitable solvent partition procedure. FT-IR, 1H-NMR and 13C-NMR were used for molecule characterization and identification. Amino acid aldehydes were successfully incorporated into a 20-mer peptide from a malarial-relevant sequence, and their impact on the molecule's conformational properties was assessed. Reduced amide isoster-bond pseudopeptides are regarded as potential components for a sub-unit based malarial vaccine. However, sequences containing isoster bonds involving asparagine or glutamine can become difficult since these precursors are obtained in yields lower than 0.5%. The current report presents a new controlled side-chain protection strategy for obtaining both aldehydes in yields higher than 80%. These synthons were successfully incorporated into malarial-relevant 20-mer peptides and their impact on the molecule's conformational properties was assessed. The MSP-1 202-221peptide 1522 native sequence in the upper and its ?-14411 analog harboring the ( 206Asn-CH 2-NH-Leu 207) isoster bond is shown at the bottom. © 2011 John Wiley and amp; Sons A/S.